Pertumbuhan Tunas Dan Akar Setek Tanaman Mawar (Rosa sp.) Akibat Konsentrasi Air Kelapa - Sogan Budi Martana; Edy Sofyadi; Sri Nur Widyastuti L. (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
Coconut water contains natural auxin growth regulators which are useful in stimulating root cuttings. This study aims to obtain the optimum of concentration of coconut water on the roses of cutting. The research was conducted from August to October 2018, in Pasir Sereh Village, Cihideung Village, Parompong District, West Bandung Regency, West Java Province. This study used a Randomized Block Design (RBD) with 6 treatments and 4 replications, namely A (Control), B (Concentration of 10% Coconut Water), C (Concentration of 20% Coconut Water), D (30% Concentration of Coconut Water), E (40% Concentration of Coconut Water), F (50% Concentration of Coconut Water). The parameters measured in this study were germination age, number of shoots, number of leaves, leaf area, root length, and root volume. The results showed no concentration optimum of coconut water which had a good effect on the growth shoot and root of stem cuttings of roses. At concentrations of 10%, 20%, 30%, 40%, and 50%, the growth shoot and root of rose cuttings was not different effect that without treatment.